Earthquakes and tsunamis in Roman Palestine: Consequences and Post-seismic Initiatives in Urban Centers Between the 1st Century BC and 4th Century AD. (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2023)
The region corresponding to Roman Palestine, crossed by the Dead Sea Fault, has been affected several times by earthquakes and tsunamis, which have periodically caused damage and destruction. Biblical, literary, and Rabbinical sources report echoes of these events. Furthermore, archaeological investigations have sometimes brought evidence and signs on architectural structures to light. Several studies have dealt with the sequence of these events based on sources. However, a broader approach still needs to be added, which examines archaeological evidence and consequences for cities and populations. This contribution, which combines analysis of literary sources and archaeological data, intends to tackle the question of the impact that seismic events have had on urban planning and city life. Additionally, considering a selection of case studies (Caesarea Maritima, Nysa-Schytopolis, Jerusalem, Ascalon, and Sepphoris), this analysis aims to investigate the reaction of local communities, their resiliency, and political initiatives. The results indicate that only the great earthquake of 363 AD significantly affected cities' civil organization and urban planning.
Keywords: Roman Palestine; Earthquake; Tsunami; Resiliency; City; Architecture